2016
DOI: 10.1177/2048872615624241
|View full text |Cite
|
Sign up to set email alerts
|

Serum potassium levels, cardiac arrhythmias, and mortality following non-ST-elevation myocardial infarction or unstable angina: insights from MERLIN-TIMI 36

Abstract: Background In acute coronary syndrome (ACS), potassium levels <3.5 mEq/L are associated with ventricular arrhythmias. Current guidelines therefore recommend a potassium target >4.0 mEq/L in ACS. Our study evaluated the association between potassium levels, cardiac arrhythmias, and cardiovascular death in patients with non-ST-segment elevation myocardial infarction or unstable angina. Methods Potassium levels were measured in 6515 patients prior to randomization to receive either ranolazine or a placebo in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

8
65
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(74 citation statements)
references
References 32 publications
8
65
0
1
Order By: Relevance
“…Potassium levels outside of the range of normal have been associated with increased risk of all-cause and cardiovascular mortality as well as cardiac arrhythmias and end-stage renal disease (ESRD). 1-6 …”
mentioning
confidence: 99%
“…Potassium levels outside of the range of normal have been associated with increased risk of all-cause and cardiovascular mortality as well as cardiac arrhythmias and end-stage renal disease (ESRD). 1-6 …”
mentioning
confidence: 99%
“…A Ushaped relationship between mean serum potassium concentration and mortality rate has been reported in the past literature. 24 As the mortality cases in our study were too small (5 cases), it is not possible to comment on the correlation of mortality and serum potassium levels. However; we observed that percentage of mortality cases increased from normokalemia group (8.57 %) to hypokalemia group (16.6 %).…”
Section: Discussionmentioning
confidence: 73%
“…6 A U-shaped relationship between the potassium levels at admission and both early and late risk of Cardiovascular death was also observed by Patel RB et al They observed lower risk of cardiovascular death in patients with admission potassium levels between 3.5 and 4.5 mEq/l. 24 Previous studies also show higher mortality in hypokalemic AMI patient in comparison to normokalemic AMI patients. 19,21 Extracellular (serum) potassium concentration is normally maintained within the approximate reference range which is important for normal cardiac function.…”
Section: Discussionmentioning
confidence: 93%
“…It is well known that the high sympathetic activity during ACS stimulates the Na þ /K þ ATPase to pump potassium inside the cell. The intracellular influx increases the resting potential, facilitating the automatic activity of the non-ischaemic myocardium and the triggering of one 4 or even many ventricular events. 5 On the other hand, the mechanism underlying the increased mortality risk in hyperkalemic patients is still a matter of debate, and no hypotheses can be extrapolated from the present meta-analysis.…”
mentioning
confidence: 99%
“…In fact, while hyperkalemia leads to reduced cardiac excitability and, therefore, to atrioventricular block, sinus arrest and pulseless electrical activity, these are usually reported for potassium levels that are higher than 5.0 mEq/l, or even more. 4 Mildly increased potassium levels may also indicate renal failure, which constitutes a major risk factor for short-term and long-term survival in ACS. Until more data are available, it is feasible to hypothesise that a mildly increased potassium concentration (4.5-5.0 mEq/l) could be a marker of disease rather than a mortality cause by itself, while higher potassium levels directly expose the ACS patient to an increased risk of asystole and pulseless electrical activity.…”
mentioning
confidence: 99%